Vitamin D supplementation and risk of stroke: A meta-analysis of randomized controlled trials - Fu, Jia; Sun, Junfang; Zhang, Chao (Frontiers in Neurology, 2022)
Background: Previous observational studies have supported the hypothesis that vitamin D supplementation protects against stroke. However, several current intervention studies contradict this observation. Therefore, we conducted a meta-analysis to investigate further the association between vitamin D supplementation and the risk of stroke. Methods: This meta-analysis was conducted in accordance with the PRISMA statement and included all prospective randomized controlled trials (RCTs) that analyzed the relationship between vitamin D supplementation and the risk of stroke. A literature search strategy was established, and the following Medical Search Terms (MeSH) were used: “vitamin D,” “Calcitriol,” “Calcifediol,” “Cholecalciferol,” “25-Hydroxyvitamin D 2,” “ergocalciferols,” “stroke,” and stroke-derived terms. We searched for articles published before January 2022 in several databases, including PubMed, Web of Science, EMBASE, and The Cochrane Library. We also reviewed references included in relevant published meta-analyses and searched the http://www.ClinicalTrials.gov website for additional prospective RCTs. The Q test and I2 were utilized to assess the degree of heterogeneity among the studies. Review Manager 5.3 and STATA16.0 software programs were used to assess the literature quality and perform statistical analyses. Results: Twenty-four prospective RCTs (86,202 participants) were included. There was no statistical heterogeneity among the prospective RCTs (I2=0.0%, P=0.94) included in this meta-analysis. We determined that vitamin D supplementation was not associated with a reduced risk of stroke compared to placebo (RR=1.02, 95%CI: 0.93-1.13, P=0.65). Results were generally comparable, based on age, sex, body mass index (BMI), follow-up period, baseline 25-hydroxyvitamin D (25(OH)D) levels, the designated endpoint, latitude, vitamin D dosage, type of vitamin D administered, and an absence or presence of concurrent calcium supplementation (P>0.05). Conclusion: Our study revealed that additional vitamin D supplementation did not reduce the risk of stroke. Therefore, additional prospective RCTs of similar design should not be encouraged to assess any association between vitamin D supplementation and reduced stroke risk.